PRZEŁOM ROKU 1956 W POLSCE A ORZECZNICTWO KARNO-ADMINISTRACYJNE - Marcin Łysko (Zeszyty Prawnicze)
THE TURNING-POINT OF 1956 IN POLAND AND THE JURISDICTION IN PETTY OFFENCES’ CASES Summary The 1956 political events in Poland had substantial influence on jurisdiction in petty offences cases. This jurisdiction was based on socialist grounds. According to the pattern, these cases were decided by collective bodies, in which lay judges were represented. The educational role of this jurisdiction was stressed, especially the punishment of corrective labor was important from this point of view. This punishment replaced the penalty of arrest. However, the results were different from the expectations. The boards judging petty offences were not able to stop the hooligans, because they couldn’t arrest them. On the other hand, they could apply the substituting penalty of arrest (from 1953) to those farmers, who did not comply with the compulsory delivery of agriculture goods. After the events of 1956 the repressive role of the jurisdiction in farmers’ cases was substantially limited. The educational measures started to play more important role. It was decided that the most important task of the judging boards is the fighting against hooligans, especially when the petty offence was committed after drinking alcohol. The substitutive penalty of arrest was reintroduced in this kind of cases and the fines were raised. The educational role of the jurisdiction was in fact eliminated and its repressive role was stressed again.